Numerical study of multiparticle scattering in λϕ 4 theory - S. V. Demidov; B. R. Farkhtdinov (Journal of High Energy Physics, 2018)
Abstract We study numerically classical collisions of waves in λϕ 4 theory. These processes correspond to multiparticle scattering in the semiclassical regime. Parameterizing initial and final wavepackets by energy E and particle numbers N i , N f we find classically allowed region in the parameter space. We describe properties of the scattering solutions at the boundary of the classically allowed region. We comment on the implications of our results for multiparticle production in the quantum regime.